Dense alumina-mullite composite ceramics from alumina and spodumene-albite feldspar binary mixtures: Processing and properties - Hernández, Maria Florencia (2020)
A processing strategy for obtaining alumina-spodumene ceramics from fine commercial powders is presented. In this work, a spodumene addition to calcined alumina powder was performed and their proportion was explored between 15 and 45 wt%. The industrial spodumene presented secondary phases, mainly albite and quartz. Mechanical properties were evaluated. Although they were lower than those of sintered alumina, based on the achieved values an adequate behavior in structural applications can be assumed, especially taking into account that the better mechanical behavior was coupled with the lower thermal expansion. Relatively low thermal expansion≈ (5 x 10-1 °C-1) behaviors were observed in one of the developed materials. Noncrystalline phases containing lithium were detected. We assume that all the lithium oxide incorporated through the spodumene is in the glassy phase after the sintering of the materials. This difference in lithium concentration in the composition of the resulting glass affected the thermal expansion of the developed materials. Particularly with low lithium content (30 wt% of additive) the material performance was enhanced. This, together with the mechanical behavior, encourages structural applications with high thermomechanical solicitations. With the information gathered, a wide range of materials with specific properties can be obtained by modulating the spodumene-alumina proportion only.